Elongation/termination factor exchange mediated by PP1 phosphatase orchestrates transcription termination - Kecman, T; Kuś, K; Heo, D; Duckett, K; Birot, A; Liberatori, S; Mohammed, S; Geis-Asteggiante, L; Robinson, C; Vasiljeva, L (Cell Press, 2018)
Termination of RNA polymerase II (Pol II) transcription is a key step that is important for 3′ end formation of functional mRNA, mRNA release, and Pol II recycling. Even so, the underlying termination mechanism is not yet understood. Here, we demonstrate that the conserved and essential termination factor Seb1 is found on Pol II near the end of the RNA exit channel and the Rpb4/7 stalk. Furthermore, the Seb1 interaction surface with Pol II largely overlaps with that of the elongation factor Spt5. Notably, Seb1 co-transcriptional recruitment is dependent on Spt5 dephosphorylation by the conserved PP1 phosphatase Dis2, which also dephosphorylates threonine 4 within the Pol II heptad repeated C-terminal domain. We propose that Dis2 orchestrates the transition from elongation to termination phase during the transcription cycle by mediating elongation to termination factor exchange and dephosphorylation of Pol II C-terminal domain.